Comparative Assessment of Physico-Chemical And Phyto-Chemical Parameters of Wild And Cultivated Chitraka (Plumbago Zeylanica Linn.) - Sudhakar, Kamdi Payal; Shamrao, Deogade Meena (International Journal of Psychosocial Rehabilitation, 2020)
Background- Major supply source of plant Chitraka (Plumbago zeylanica Linn.) is Wild. This plant grows slowly and it takes long time until the roots become mature enough for medicine preparation. As mostly root of Chitraka is used in Ayurvedic medicine, it needs to be uprooted and so it becomes impossible to maintain the sustainability of a plant. So, it needs to examine, the potency of leaves and stem of the plant as compare to its root so that the plant can be saved and one can also get the same therapeutic efficacy. Another important point of the study is related to the use of the cultivated source of Chitraka instead of the wild source because a large scale of the harvest is getting removed from the forest through illegal route and so that this important plant can be saved from extinction. Aim and objective - To study the comparative physico-chemical and phyto-chemical parameters of root, stem and leaves of the wild and the cultivated source of Chitraka. Material and Method – For this prospective study Chitraka plants will be collected from field and Herbal garden, MGACH&RC, Salod (H), Wardha and conclusion will be drawn by studying HPTLC to analyze the level of Plumbagin in root, stem and leaves of wild and cultivated source of plant by comparing with the standard marker. Results-On the basis of Physicochemical and Phytochemical analysis, the phytoconstituent (Plumbagin) concentration in leaves, stem and root will be concluded. Conclusion- The result will depict either we can use the leaves and stem of Chitraka instead of root and similarly the cultivated source of the plant instead of the wild source. The positive result will help to preserve and save the plant Chitraka.